2019
DOI: 10.9734/ajsspn/2019/v4i330047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Organic and NPK Fertilizers on the Growth and Yield of Sweet Potato (Ipomoea batatas (L) Lam) in the Centre of Côte d’Ivoire

Abstract: In Côte d’Ivoire, the sweet potato is little cultivated but stays however a culture of pension and a food mattering in certain regions. This study was conducted to assess the effect of the application of mineral (NPK 15-15-15, NPK 12-22-22) and organic (poultry manure) fertilizers on yield components of sweet potato (Ipomoea batatas (L) Lam). The experiment was conducted over two years (2016 to 2017) in experimental station of National Center of Agronomic Research (CNRA) of Bouaké in the centre of Côte d'Ivoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Although no relationship was found between the yield of the two varieties probably related to the small sample size (60), many other studies elsewhere showed that production yields are influenced by variety [15]. Sidiky et al, [16] studied the effects of different doses of mineral fertilizer on the yield of two varieties of potato in Bouaké, central Ivory Coast, and reported that the yield varied from 9.68 to 15.15 t/h depending on the variety and the dose of fertilizer used. This variability in yield according to variety suggests that these varieties have different genotypic [7,13] and are cultivated in the rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…Although no relationship was found between the yield of the two varieties probably related to the small sample size (60), many other studies elsewhere showed that production yields are influenced by variety [15]. Sidiky et al, [16] studied the effects of different doses of mineral fertilizer on the yield of two varieties of potato in Bouaké, central Ivory Coast, and reported that the yield varied from 9.68 to 15.15 t/h depending on the variety and the dose of fertilizer used. This variability in yield according to variety suggests that these varieties have different genotypic [7,13] and are cultivated in the rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulative effect of potassium in this respect may be attributed to its function in plants which include energy metabolism and enzyme activation on exchange rate and nitrogen activity, as well as its role in enhancing carbohydrates movement and translocation from shoot to storage organs, consequently increase the tuber weight (Marscher, 1995and 2012, as well as Howeler, 2014. In general, potassium is essential for the production of sweet potato which its improvement aerial biomass fresh weight that reflected on high translocation assimilates and accumulated in the store tuber roots (Sidiky et al .,2019). Foliar application of different potassium sources, i.e.…”
Section: Tuber Yield and Its Componentmentioning
confidence: 99%
“…For these 3 varieties, the best timing to take cuttings from the mother plant in order to get high-yielding planting material was still a mystery. However, research showed that cuttings taken from Anggun 3 at the time of 3-3.5 months after planting (MAP) gave a higher yield (Nurul Atilia Shafienaz, et al [15]). Though inorganic fertilizers help to enhance the vegetative and storage parameters of sweet potatoes, they are not readily available or may be too expensive to use by the poor farmer.…”
Section: Introductionmentioning
confidence: 99%